2015
DOI: 10.1016/j.pmrj.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Muscles Activation Pattern During Walking in Subjects With and Without Chronic Low Back Pain: A Systematic Review

Abstract: Individuals with chronic LBP exhibit higher global trunk muscle activity. However, the activation pattern appears to vary depending on subphases of gait. It seems that increased walking velocity challenges the stability of the spine and the control system increases muscular activation and variability level to cope with this problem. Further standardized studies with subtyped LBP cases are needed to clarify the controversial findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 53 publications
4
47
0
3
Order By: Relevance
“…A systematic review investigating the activation pattern of trunk muscles during walking in subjects with and without LBP indicated that those with LBP exhibit higher ES activity compared with asymptomatic subjects 20. The magnitude of the decreases in erector spinae activity and the low back extension moment while wearing an ORF is relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review investigating the activation pattern of trunk muscles during walking in subjects with and without LBP indicated that those with LBP exhibit higher ES activity compared with asymptomatic subjects 20. The magnitude of the decreases in erector spinae activity and the low back extension moment while wearing an ORF is relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…Nossos resultados se assemelham a diversos outros estudos que discorrem que pacientes com dores crônicas, como fibromialgia e dor lombar, apresentam também redução na velocidade da marcha e comprimento do passo quando comparados à indivíduos saudáveis [15][16][17][18] . Este padrão alterado de marcha pode contribuir para redução das atividades funcionais diárias do indivíduo 15 , além de predizer possíveis sintomas depressivos e comprometimentos cognitivos [19][20][21] .…”
Section: Discussionunclassified
“…Acredita-se que a influência de fatores psicológicos sobre as disfunções musculares encontradas em indivíduos com dores crônicas ainda não está bem esclarecida 16 , o modelo fear-avoidance traz que a catastrofização e o medo da dor e subsequente evitação de atividades que exacerbam a queixa, acarreta em redução do nível de atividade física e, consequentemente, contribui para as alterações nos parâmetros da marcha 15,23 e nos padrões do sistema motor 15,24 . Embora não tenhamos notado nenhuma correlação entre quaisquer variáveis da marcha com o TAMPA, foi possível observar que o grupo com dor obteve maior escore na escala de cinesiofobia (TAMPA) quando comparadas ao grupo controle.…”
Section: Discussionunclassified
“…Low back pain (LBP) is associated with altered motor control and muscle activity. A number of studies have shown a link between LBP and delayed muscle onsets [1], lower level of motor variability [2], reduced muscle activation of the trunk, increased stiffness [3], lower muscle force [4], changes in muscles' voluntary activity [5] and higherordered movement capacities, such as gait [6,7]. Interestingly, although all of these behavioural features have their own underlying physiological changes (e.g.…”
Section: Introductionmentioning
confidence: 99%